2001
DOI: 10.1002/ajh.10011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of RDW value in differential diagnosis of hypochrome anemias

Abstract: Red cell distribution width (RDW) was studied in adults carrying d-b thalassemia traits (db-TT) who were 20±40 years of age (n = 29), b thalassemia traits (b-TT) with an age range of 18±60 years (n = 49), iron de®ciency anemia (IDA) in individuals aged 1±18 years (n = 27), and in controls with an age range of 20±40 years (n = 20). Although red blood cell count, MCV, and MCH values showed no statistically signi®cant differences between db-TT and b-TT, the mean RDW value was signi®cantly higher in db-TT (20.14 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 5 publications
3
49
0
10
Order By: Relevance
“…RDW values are increased in hemolytic anemia, in the case of erythrocyte transfusion, and deficiency of vitamin B 12 , folic acid and iron. 9,11,12 Many studies have shown a correlation between higher RDW values and prognosis, but these studies were about cardiovascular and cerebrovascular diseases, chronic renal failure, liver disease, pancreatitis and venous thromboembolism. [13][14][15][16][17] Kurt et al showed a correlation of nonvalvular atrial fibrillation and higher RDW values in 320 patients.…”
Section: Discussionmentioning
confidence: 99%
“…RDW values are increased in hemolytic anemia, in the case of erythrocyte transfusion, and deficiency of vitamin B 12 , folic acid and iron. 9,11,12 Many studies have shown a correlation between higher RDW values and prognosis, but these studies were about cardiovascular and cerebrovascular diseases, chronic renal failure, liver disease, pancreatitis and venous thromboembolism. [13][14][15][16][17] Kurt et al showed a correlation of nonvalvular atrial fibrillation and higher RDW values in 320 patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 In our study, all hematological indexes of the MA and A groups became similar to controls at the end of three-month iron treatment, except the persistently higher RDW value. As we can't definitely explain the reason of elevated RDW values at the end of the followup, we believe that probably longer time than previously reported is needed for normalization of RDW.…”
mentioning
confidence: 65%
“…35 En nuestro estudio, todos los índices hematológicos de los grupos DA y A alcanzaron valores similares a los de los controles al final de los tres meses de tratamiento con hierro, excepto el valor persistentemente elevado de ADE. Dado que no es posible explicar decididamente el motivo de los valores elevados de ADE al final de estudio, consideramos que es posible que se necesite un período más prolongado que el informado previamente para lograr la normalización de la ADE.…”
Section: Discussionunclassified